(untitled) - DeWolf, Lotan Harold; (1905-1986) (U.S.A, 1959)
L. Harold DeWolf's book is part of a trilogy written at about the same time. The others are The Case for A New Reformation Theology by William Hordern and The Case for Orthodox Theology by Edward J. Carnell. The set is priceless for one to read today and find the value in each case as presented by thoughtful, solid, presentations. They are intended to provide for the readers with a clear statement of three contemporary theological viewpoints by convinced adherents to these positions.
Keywords: Dogmatic theology